Tomografia computadorizada de tórax em crianças : podemos fazer um exame com a dose semelhante a de um raio x de tórax e sem anestesia? - Dorneles, Cristina Manera (2016)
Objective: To evaluate the technical quality of low-dose computed tomography without contrast and without the use of anesthesia in the diagnosis of lung diseases in children Materials and Methods: It reviewed 86 chest CT scans performed due to clinical indications of acute or chronic inflammatory lung diseases, cancer or congenital malformations in patients from 1 to 18 years of age who were subjected to a low dose of radiation dose bellow the dose recommended by the ALARA and using interactive image reconstruction filters performed without the use of anesthesia or sedation. The exams will be evaluated by two reviewers and age, gender, the radiation dose, image quality and image noise will be assessed. Image analysis will be quantitative. The variables will be the outside Roi diameter of trachea divided by the Roi of trachea, the percentage of axial images with motion artifacts, and identification of the tracheal, the main and segmental bronchi– 20 segments, the main and lobar pulmonary arteries and the ascending aorta artery. The presence of pleural effusion and the identification of paratracheal and subcarinal lymph node chains will also be assessed. Data will be analyzed by for mean, standard deviation and the correlation of the data will be analyzed by tests of Pearson and Spearman, considering significant a p<0.05. Results: The average age of the patients was 5.5 years. LSD as well with the LID, LSE and LIE were displayed in all tests. The middle lobe in almost all (n = 85) apical segment and the medial basilar segment were seen in almost all of the scans (n = 84). The aorta and pulmonary arteries were distinguished on all tomography examinations. The percentage of images with motion artifact introduced an average of 0.8 with IC: 0-2.9 (P25-P75) with p < 0.001. The noise of the image showed an average of 45.5 with 12.4DP. How much ROI the trachea and main bronchi were seen in all the CT scans. The image quality was considered excellent and blurring that didn't compromise the evaluation in almost all the tests. The DLP in mGy dose presented an average of 27.5 with DP ± 11.1. Conclusion: The dose used was significantly lower than the one used in children and allowed the visualization of lung structures in almost all patients, enabling the final diagnosis of cystic fibrosis, bronchiolitis and congenital malformations without difficulty of diagnosis by image artifact